Antioxidant and Cytotoxic Activities of Rhizome and Fruit Extracts of Susube (Meistera aculeata (Roxb.) Škorničk. & M.F. Newman) from Southeast Sulawesi. - Megawati, Megawati; Alif, Alfiah; Sabandar, Carla Wulandari (Hasanuddin University, 2025)
Susube (Meistera aculeata (Roxb.) Škorničk. & M.F.Newman) is one of the species of the zingiberaceae family that grows in Southeast Sulawesi, especially in Konawe Regency. The fruit of this plant is often consumed and used as a cooking spice by the native. Meanwhile, the compounds content and bioactivity of the rhizome and fruit which is a characteristic of the Zingiberaceae family, has never been reported. Therefore, this study aimed to identify compounds contained in the rhizome along with their antioxidant and cytotoxic properties. The research method used is experimental research, starting with qualitative phytochemical screening in ethanol exctract and then continued with antioxidant (1,1-diphenyl-2-picrylhydrazyl or DPPH) and cytotoxicity assay (Brine Shrimp Lethality Test or BSLT). The results of the phytochemical screening indicate that the ethanol extract of the Susube rhizome and fruit contains alkaloids, flavonoids, tannins, terpenoids, and saponins. Antioxidant activity was determined based on the ability to reduce DPPH radicals and was calculated by determining the IC50 value, while toxicity was assessed based on shrimp larvae mortality and calculated by determining the LC50 value. The study results show that the IC50 values for the ethanol extract of Susube rhizome, fruit and the positive control ascorbic acid are 4.9 µg/mL, 4,5 µg/mL and 2.2 µg/mL, respectively. Meanwhile, the LC50 values for the ethanol extract of Susube rhizome, fruit, and the positive control potassium bichromate are 578 µg/mL, 958 µg/mL, and 2.8 µg/mL, respectively. Based on these results, it can be concluded that the ethanol extract of Susube rhizome and fruit (Meistera aculeata (Roxb.) Škorničk. & M.F.Newman) exhibits toxic effects on shrimp larvae (≤1,000 mg/L). Additionally, its ethanol extract shows very strong antioxidant effects in scavenging DPPH free radicals. Therefore, this study suggests that the Susube rhizome and fruit extract warrants further investigation as a promising candidate for treatment or prevention of diseases, supporting the potential of Southeast Sulawesi's local natural resources for phytopharmaceutical or herbal medicine